Glycolytic potential and ultimate muscle pH values in red deer (Cervus elaphus) and fallow deer (Dama dama) - Wiklund, Eva; Manley, Timothy R.; Littlejohn, Roger P. (Rangifer, 2004)
The ultimate pH value of meat (measured at approx. 24 hours post slaughter) gives information about the technological quality, i.e. shelf life, colour, water-holding properties and tenderness and is a direct consequence of muscle glycogen (energy) levels at slaughter. It may therefore also indicate whether or not the animal has been exposed to stressful energy depleting events prior to slaughter. In the present study, 141 animals (130 red deer (Cervus elaphus) and 11 fallow deer (Dama dama) were included to investigate the relationship between ultimate pH and residual glycogen concentration in red deer and fallow deer M. longissimus. In addition, the muscle glycogen content and ultimate pH values in three red deer muscles (Mm. triceps brachii, longissimus and biceps femoris) were studied. M. triceps brachii had higher ultimate pH and lower glycogen content compared with the other two studied muscles. The frequency of intermediate DFD (5.8≤ pH
Keywords: DFD; glycogen; meat quality; nutritional status; pre-slaughter stress; venison